2015
DOI: 10.1002/anie.201503031
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Replenishable Anti‐Waxing Organogel Materials

Abstract: Solid deposition, such as the formation of ice on outdoor facilities, the deposition of scale in water reservoirs, the sedimentation of fat, oil, and grease (FOG) in sewer systems, and the precipitation of wax in petroleum pipelines, cause a serious waste of resources and irreversible environmental pollution. Inspired by fish and pitcher plants, we present a self‐replenishable organogel material which shows ultra‐low adhesion to solidified paraffin wax and crude oil by absorption of low‐molar‐mass oil from its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 76 publications
(52 citation statements)
references
References 41 publications
0
52
0
Order By: Relevance
“…In addition to the liquid-infused porous structure based slippery surfaces, organogel-based slippery surfaces [ 62,[67][68][69][70][71] have been also developed and utilized for anti-biofouling. Yao et al reported lubricant-swollen fl uorogels by photocuring perfl uorinated alkyl acrylate monomers (2-perfl uorooctylethyl acrylate (PFOEA) or 2-perfl uorohexylethyl acrylate (PFHEA)) and fl uorinated macromolecular crosslinker (perfl uoropolyether dimethacrylate (PFPE-DMA)) and subsequently swelling with fl uorinated lubricants (FC-70).…”
Section: Bioinspired Slippery Surfacesmentioning
confidence: 99%
“…In addition to the liquid-infused porous structure based slippery surfaces, organogel-based slippery surfaces [ 62,[67][68][69][70][71] have been also developed and utilized for anti-biofouling. Yao et al reported lubricant-swollen fl uorogels by photocuring perfl uorinated alkyl acrylate monomers (2-perfl uorooctylethyl acrylate (PFOEA) or 2-perfl uorohexylethyl acrylate (PFHEA)) and fl uorinated macromolecular crosslinker (perfl uoropolyether dimethacrylate (PFPE-DMA)) and subsequently swelling with fl uorinated lubricants (FC-70).…”
Section: Bioinspired Slippery Surfacesmentioning
confidence: 99%
“…Supramolecular gels, a type of self‐assembled material, have received a great deal of attention due to their potential applications in biomaterials, catalyzers, electronic devices, templates for nanostructures, sensors, drug carriers, and oil recovery . Supramolecular gels are generated by self‐assembly of the gelator in organic solvent or water through intermolecular noncovalent interactions, such as hydrogen bonding, hydrophobic interactions, coordination bonds, electrostatic interactions, π–π stacking, van der Waals forces, charge‐transfer interactions, and metal–ligand coordination . These noncovalent interactions can provide highly organized molecular architectures that display reversible, instant, and visual changes in response to external stimuli, such as ultrasound, shearing stress, light, heating, magnetism, ions, pH, chiral compounds, enzymes, and gases.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17][18][19][20] Supramolecular gels are generated by self-assembly of the gelator in organic solvent or water through intermolecular noncovalent interactions, such as hydrogen bonding, hydrophobic interactions, coordinationb onds, electrostatic interactions, p-p stacking, van der Waals forces, charge-transfer interactions,a nd metal-ligand coordination. [21][22][23][24][25] These noncova-lent interactions can provide highly organized moleculara rchitectures that display reversible, instant,a nd visual changes in responset oe xternals timuli, such as ultrasound, shearing stress, light, heating,m agnetism,i ons, pH, chiral compounds, enzymes,a nd gases. Typically,s upramolecular gels are formed by heatingalow-molecular-weight (LMW) gelator in an appropriate solvent at as pecific concentration, then cooling.…”
Section: Introductionmentioning
confidence: 99%
“…[121] Of note, the hydrogels used for adhesives were reviewed recently [122][123][124][125] and will be not discussed herein. [127] Due to the existence of the thin oil surface layer, the adhesion of solidified paraffin wax on the organogel surface was more than 500 times lower than that of conventional material surfaces. [126] Yao et al presented a self-replenishable PDMS organogel swollen with petroleum, showing sustainable ultralow adhesion to solidified paraffin wax and crude oil by absorption of low-molar-mass oil from its crude-oil environment (Figure 10b).…”
Section: Antisolid Adhesionmentioning
confidence: 99%
“…[126] Yao et al presented a self-replenishable PDMS organogel swollen with petroleum, showing sustainable ultralow adhesion to solidified paraffin wax and crude oil by absorption of low-molar-mass oil from its crude-oil environment (Figure 10b). [127] Copyright 2015, John Wiley & Sons, Inc. c) Self-replenishing organogel surface for adaptive antisolid adhesion by the stimulus-responsive release of liquids. The shear stress of the wax was only 0.5 kPa on such organogel surface, leading to its easy-sliding under flow conditions.…”
Section: Antisolid Adhesionmentioning
confidence: 99%